1998
DOI: 10.1021/jp982483n
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Proton Transfer of 1-Naphthol in Micelles

Abstract: The fast deprotonation of 1-naphthol, which occurs in 35 ps in aqueous solution, is studied in neutral (triton X 100, reduced, TX-100R), cationic (cetyl trimethylammonium bromide, CTAB), and anionic (sodium dodecyl sulfate, SDS) micelles. Drastically different effects on the proton transfer process and the relative emission intensities of the neutral form (360 nm) and the anion (460 nm) are observed in the three micelles. The intensities of the anion and the neutral emission of 1-naphthol exhibit a break aroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 40 publications
3
83
1
Order By: Relevance
“…On the contrary, the high ionic strength at the interface and the small amount of water make the proton-transfer process extremely slow in comparison with bulk water. [55] On the other hand, when W 0 is larger than 8-10 and the amount of water is enough to create the water pool with relatively free water molecules, [1,2,19] the processes can be described as those shown in Scheme 1. It should be noted that in this situation and because of the electrostatic repulsion between the phenolates species and the negative AOT RM interface, it is likely that the acid-base equilibrium takes place only at the water pool of the RMs.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, the high ionic strength at the interface and the small amount of water make the proton-transfer process extremely slow in comparison with bulk water. [55] On the other hand, when W 0 is larger than 8-10 and the amount of water is enough to create the water pool with relatively free water molecules, [1,2,19] the processes can be described as those shown in Scheme 1. It should be noted that in this situation and because of the electrostatic repulsion between the phenolates species and the negative AOT RM interface, it is likely that the acid-base equilibrium takes place only at the water pool of the RMs.…”
Section: Resultsmentioning
confidence: 99%
“…4a-c) [29]. The lifetime of 2BBI in an aqueous solvent is found to be tri-exponential with the values 60 ps (0.79), 600 ps (0.13) and 4000 ps (0.08) and on the addition of CTAB (15 mM) to this solution all the three lifetime components change.…”
Section: Time-resolved Emissionmentioning
confidence: 86%
“…More dramatic retardation has been observed in the case of solvation dynamics. While the solvation dynamics of water molecules occurs on the subpicosecond timescale in ordinary water, it is retarded by at least three orders of magnitude to the nanosecond timescale inside cyclodextrin cavities, micelles and microemulsions [97]. It has been demonstrated that in aqueous solution the rate of deprotonation of protonated aminopyrene increases nearly 3 times when the probes bind with cyclodextrin, while for 1-naphthol the deprotonation becomes almost 20 times slower.…”
Section: Espt Of Hydroxyaromatic Compounds In Organized Media and Sommentioning
confidence: 99%